2016
DOI: 10.1111/cge.12839
|View full text |Cite
|
Sign up to set email alerts
|

Muscular dystrophies and myopathies: the spectrum of mutated genes in the Czech Republic

Abstract: Inherited neuromuscular disorder (NMD) is a wide term covering different genetic disorders affecting muscles, nerves, and neuromuscular junctions. Genetic and clinical heterogeneity is the main drawback in a routine gene-by-gene diagnostics. We present Czech NMD patients with a genetic cause identified using targeted next-generation sequencing (NGS) and the spectrum of these causes. Overall 167 unrelated patients presenting NMD falling into categories of muscular dystrophies, congenital muscular dystrophies, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 8 publications
5
16
1
Order By: Relevance
“…After confirming the consistency of these results with the clinical and pathological characteristics of the patients, highly probable pathogenic genotypes could be identified in 50 out of 72 cases (68.5%). The above results gave a similar diagnostic rate to other recent NGS (next-generation sequencing) studies in genetically undiagnosed cohorts of LGMD: 47% in the Czech Republic, 62% in China, and 76% in Saudi Arabia [ 27 29 ]. Lower yields have been reported in studies involving patients pre-screened by targeted gene sequencing: 33% in Germany, 40% in the USA, and 45% in Australia [ 30 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…After confirming the consistency of these results with the clinical and pathological characteristics of the patients, highly probable pathogenic genotypes could be identified in 50 out of 72 cases (68.5%). The above results gave a similar diagnostic rate to other recent NGS (next-generation sequencing) studies in genetically undiagnosed cohorts of LGMD: 47% in the Czech Republic, 62% in China, and 76% in Saudi Arabia [ 27 29 ]. Lower yields have been reported in studies involving patients pre-screened by targeted gene sequencing: 33% in Germany, 40% in the USA, and 45% in Australia [ 30 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…Overall, in this series of 352 patients, 138 pathogenic or likely pathogenic variants were identified, among which 26 CNVs, and 22 variants of uncertain significance. Our approach revealed to be a useful strategy, providing a molecular diagnosis in 35.2% of patients, similar to other heterogeneous conditions (50% for inborn errors of metabolism (Yubero et al, ), 47.3% for myopathies and muscular dystrophies (Stehlikova et al, ), 39% for intellectual disability (Martinez et al, ), 28.5% for epileptic encephalopathy (Kothur et al, ), 28.1% for disorders of sexual development (Fan et al, ), 24.5% for developmental eye disorders (Patel et al, ), 20% for primary arrhythmia syndrome and cardiomyopathy (Robyns et al, ), and 18% for inherited polyneuropathy (Wang et al, ). A 7.7% increase was observed in our diagnostic performance, compared to our previous workflow (diagnostic yield 27.5% before 2014, data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…CLM are a diagnostic challenge due to their variable expressivity, clinical overlap between the different syndromes (e.g., radial anomalies) and their genetic heterogeneity. NGS approaches are increasingly being used for genetic diagnosis in routine clinical practice and many publications report successful use in heterogeneous disorders such as inborn errors of metabolism (Yubero et al, ), neuromuscular disorders (Stehlikova et al, ), and intellectual disability (Martinez et al, ). To our knowledge, no report of the diagnostic impact in patients affected with CLM using high‐throughput sequencing has been published so far.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to previous studies, we observed a high genetic heterogeneity among diagnoses. [29][30][31][32] Of interest, the genes most commonly represented among the confirmed diagnoses were similar between children and adults, with DMD, RYR1, CAPN3, PYGM, DYSF, and FKRP accounting for 50% and 58% of diagnoses in children and adults, respectively. The previous large LGMD US study identified CAPN3, DYSF, and FKRP as the 3 major contributing genes, associated with 17%, 16%, and 9% of diagnoses, respectively, but DMD was only found in 4%, whereas RYR1 and PYGM were not tested.…”
Section: Discussionmentioning
confidence: 99%